PENERAPAN SYARIAT ISLAM DALAM BINGKAI KEBERAGAMAN NUSANTARA - Iqbal Maulana; Yuni Roslaili (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2018)
The implementation of the Islamic Law in Aceh received recognition from the Government of Indonesia since 1959 based on the Decree of the Deputy Prime Minister of the Republic of Indonesia No. 1 / Missi / 1959. Since then until the enactment of the BAL in 2006, several aspects of national law have become different in Aceh. This then sparked controversy, especially regarding the position of Non-Muslims and religious freedom. This article tries to explain how the application of Islamic Law in Aceh in relation to the Non-Muslim population and its solution. The study found that the relationship between Muslims and Non-Muslims in Aceh, especially in the social aspects of society, took place harmoniously. The application of Islamic Law in Aceh only applies to Muslims and there is no coercion for Non-Muslims. In this case, according to the author, it also offers the concept of "Conducted by Waliya Dien" in addressing religious plurality in Aceh, and the attitude of making Pancasila as "Kalimatun Sawa’ in the corridors of living in a state.